The Influence of Word of Mouth, Competitive Advantage and Brand Image on the Decision to Use Expeditionary Services: Pengaruh Word Of Mouth, Keunggulan Bersaing Dan Brand Image Terhadap Keputusan Menggunakan Jasa Ekspedisi - Meida Ratna Sari; Mudji Astuti (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine and analyze the influence of word of mouth, competitive advantage and brand image on the decision to use expedition services at PT. Lintas Samudra Jaya Express. The research uses a quantitative approach. The population in this study are customers who are bound by a contract with PT. Lintas Samudra Jawa Express, while the probability sampling technique using the Slovin formula, obtained a sample of 93 respondents. The data analysis technique was carried out using multiple linear regression, and hypothesis testing was carried out by partial test, simultaneous test and multiple determination coefficient test with the help of SPSS version 25 program. The results showed that: 1) word of mouth influenced the decision to use expedition services, 2 ) competitive advantage affects the decision to use expedition services, 3) brand image affects the decision to use expedition services, and 4) word of mouth, competitive advantage and brand image affect the decision to use expedition services at PT. Lintas Samudra Jaya Espress.